Speech Acts and Politeness Strategies in Gita Wirjawan-Maudy Ayunda Podcast - Rini Marliana (Lingua Franca, 2025)
The rise of podcasting has created new arenas for public intellectual discourse in Indonesia, characterized by unique interactional dynamics. This study investigates the pragmatic mechanisms that underpin these conversations, focusing on how communicative actions are performed and how interpersonal relationships are managed. Using a qualitative case study design, this research conducts a pragmatic analysis of the 'Endgame' podcast interview between host Gita Wirjawan and guest Maudy Ayunda. The study employs two key theoretical frameworks: Searle's Speech Act Theory and Brown and Levinson's Politeness Theory, interpreted through a contemporary lens. The analysis identifies the predominant speech acts used to construct the discourse and the politeness strategies employed to maintain face and foster a collaborative atmosphere. Findings indicate a high frequency of Assertive speech acts by Maudy Ayunda to establish expertise and present arguments, and Directive speech acts by Gita Wirjawan to guide the conversation. Crucially, these acts are consistently mitigated by sophisticated politeness strategies. Positive politeness (e.g., agreeing, showing admiration) builds rapport. In contrast, negative politeness (e.g., hedging, questioning, using indirectness) is employed to soften potentially face-threatening acts like disagreement or probing personal topics. This study concludes that the intellectual nature of the conversation is co-constructed through the content and a skillful interplay of speech acts and politeness strategies that allow for exploring complex and potentially sensitive ideas while preserving mutual respect and collaborative harmony.